Annual Plan 2004-05 Planning Commission Government of India - Planning Commission (Planning Commission, 2004)
The Tenth Five Year Plan has been formulated in the backdrop of visionary planning and lays foundation for national development in pursuit of the growth blueprint articulated in the India Vision 2020 document. Though India has been one of the ten fastest growing economies in the world, the Plan aims to take the country even further ahead. This aspiration has emerged from a set of macro economic indicators like rapid rise in educational level, high rates of technological innovations and applications, greater availability and access to information and phenomenal growth of service sector contributing to a reasonable confidence in growth potential.
Planning Commission Government of India
Planning Commission Government of India